SuperMensch : the legend of Shep Gordon [videorecording (DVD)] - Myers, Mike, 1963-; Myers, Mike, 1963- (2014)
Recounts the career and times of talent manager and Hollywood insider Shep Gordon, told through interviews with Shep Gordon himself as well as Alice Cooper, Emeril Lagasse, Michael Douglas, Anne Murray and many of his other clients and friends.